Supply Chain Performance Evaluation for Songket Pandai Sikek SMEs: A Case Study of Rumah Songket Lima Saudara - Ghina Haura Tsamarah; Devi Maulida Rahmah; Efri Mardawati; Amelia Hariry (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
The clothing and leather, food and chemical industries are small and medium enterprise (SME) sectors that play an important role in the economy of Tanah Datar Regency, West Sumatra. X Koto District dominates 71.2% of the clothing and leather industry business units, especially in Nagari Pandai Sikek which is famous for the production of Songket Pandai Sikek. As time goes by, the use of songket is no longer limited to traditional events, but also as a wider fashion product. Although the Songket Pandai Sikek industry continues to grow, challenges are still faced, such as high worker turnover and lack of utilization of marketing technology. The supply chain performance scores in Rumah Songket Lima Saudara in 2023 and 2024 respectively were 94.55 and 94.06 which fit in Excellent category, but the business had weaknesses in excess inventory and production volume. Strategies that can be implemented to strengthen the weaknesses include recruiting social media strategist employees, giving forecasting training for financial manager, improving customer relationship, implementing reward system for workers, creating detailed financial records and collaborating with similar businesses.